Pemanfaatan Media Digital Berbasis Realita Kehidupan dalam Pembelajaran Pendidikan Pancasila pada Siswa Sekolah Dasar - Ardiawan, I Ketut Ngurah; Luh Sukertiasih (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2026)
This study aims to analyze the use of life-based digital media in Pancasila Education learning among elementary school students in the era of globalization. The study employs a qualitative approach with a descriptive method, with analysis grounded in Media Richness Theory (MRT), which emphasizes the effectiveness of media in conveying information through message clarity, interactivity, and the ability to reduce ambiguity. Data were collected through interviews and observations in the elementary school setting. The findings indicate that digital media, such as interactive learning videos and simulations, possess a high level of media richness, thereby enhancing students’ understanding, motivation, and engagement. Additionally, such media facilitate the connection between learning materials and real-life contexts, supporting the contextual internalization of Pancasila values. However, its implementation still faces challenges related to teacher readiness, the availability of facilities, and instructional planning. This study contributes to strengthening the application of Media Richness Theory in life-based Pancasila Education learning, suggesting that the use of digital media can serve as an effective strategy to improve the quality of learning and reinforce students’ character development in elementary schools.